(268) نحو إطار متكامل لقياس ودراسة أثر أهداف التنمية المستدامة لما بعد 2015 على أوضاع التنمية المستدامة فى مصر خلال الفترة 2015-2030 Towards an Integrated Framework to Measure and Study The Impact of The Sustainable Development Goals post-2015 on the Sustainable Development in Egypt During the Period 2016-2030 - ماجد خشبة.; على نصار; هدى النمر; علاء زهران; خالد عطية (معهد التخطيط القومي،, 2018)
يوليو 2016.